2021
DOI: 10.3889/oamjms.2021.6472
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Rheumatoid Arthritis and PADI4, PTPN22, and HLA-DRB9 Genes Distribution in the Kazakhstan Population

Abstract: BACKGROUND: The prevalence of rheumatoid arthritis (RA) is 1% in the global population. The lack of epidemiological studies in developing countries makes it difficult to obtain a complete global epidemiological picture of RA. RA develops due to the interaction of multiple genetic and environmental factors, though the contribution of these factors to the various disease occurrence seen in different populations is unclear. AIM: The aim of our study was to analyze the dynamics of the general prevalence and inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Recently, we published a study on HLA-DRB9, PADI4, and PTPN22 gene distribution in Kazakhstani RA patients, which revealed, among other data, an association of PADI4 with the ACPA-positive form of RA [ 29 ]. Similar to what was found in this study, PTPN22 did not show any association with RA, RF-positive, or ACPA-positive status [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we published a study on HLA-DRB9, PADI4, and PTPN22 gene distribution in Kazakhstani RA patients, which revealed, among other data, an association of PADI4 with the ACPA-positive form of RA [ 29 ]. Similar to what was found in this study, PTPN22 did not show any association with RA, RF-positive, or ACPA-positive status [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CTLA4 (cytotoxic T-lymphocyte associated protein 4) sends the inhibitory signal to T cells and provides its regulation [ 15 ], STAT4 (signal transducer and activator of transcription 4) provides phosphorylation in response to proinflammatory cytokines and activates the transcription process under the interleukin-12 control [ 16 ], TAGAP (T cell activation Rho GTPase activating protein) regulates T-cell activation effecting its cytoskeleton [ 17 ], COG6 (component of oligomeric Golgi complex 6) provides a Golgi apparatus functioning [ 18 ], TRAF1 (tumor necrosis factor receptor-associated factor-1) encoding the certain protein of TNF superfamily mediates the antiapoptotic signals coming from TNF receptors [ 19 ], ETS1 (proto-oncogene 1, transcription factor) encodes a protein responsible of a large number of gene expression leading to stem cells and tumor process development [ 20 ], FCRL3 (Fc receptor like-3) encodes a protein that is an Fc receptor-like glycoprotein capable of influencing the activation of immunoreceptor-tyrosine [ 21 ], LBH (limb bud and heart development) regulates WNT signaling pathway [ 22 ], and the roles of LINC01104 (long intergenic nonprotein coding RNA 1104) and other genes are being investigated. Further studies aimed at validating early identified SNPs in different populations demonstrated significant variabilities in genetic predisposition to RA in various ethnicities [ 8 , 23 – 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of SNPs have been detected in the non-MHC genes, such as PTPN22 and MHC genes like HLA-DRB-1 which are potent and can drive inflammatory response in RA. Many studies revealed >150 SNPs in RA located at more than 70 gene loci (Jalil, et al, 2013-Issilbayeva, et al, 2021.…”
Section: Introductionmentioning
confidence: 99%